Meta-Analysis: The Effect of HIV/AIDS in Pregnant Women Against the Incidence of Low Birth Weight and Preterm Birth - Neti Husaeni; Cusmarih Cusmarih (Global Health Science Group, 2023)
Pregnancy poses a major challenge to immune system regulation. Immune function is suppressed in both HIV-infected and non-HIV-infected women. Transmission of the virus has also been reported to occur between mothers to fetuses. So that HIV infection can reduce the quality of pregnancy outcomes such as low birth weight babies (low birth weight) and premature birth (preterm) The purpose of this meta-analysis is to estimate the strength of the effect of HIV infection on the incidence of low birth weight babies and preterm delivery. This study is a systematic review and meta-analysis. Primary data is retrieved through the electronic databases PubMed, Science Direct, Web of Science, Springer Link and Cochrane Database. search keywords